Design, fabrication, and characterization of broad beam transducers for fragmenting large renal calculi with burst wave lithotripsy - Randad, Akshay (J Acoust Soc Am, 2020)
Burst wave lithotripsy (BWL) is a technology for comminuting urinary stones. A BWL transducer's requirements of high-pressure output, limited acoustic window, specific focal depth, and frequency to produce fragments of passable size constrain focal beamwidth. However, BWL is most effective with a beam wider than the stone. To produce a broad-beam, an iterative angular spectrum approach was used to calculate a phase screen that was realized with a rapid prototyped lens. The technique did not accurately replicate a target beam profile when an axisymmetric profile was chosen. Adding asymmetric weighting functions to the target profile achieved appropriate beamwidth. Lenses were designed to create a spherically focused narrow-beam (6 mm) and a broad-beam (11 mm) with a 350-kHz transducer and 84-mm focal depth. Both lenses were used to fragment artificial stones (11 mm long) in a water bath, and fragmentation rates were compared. The linearly simulated and measured broad beamwidths that were 12 mm and 11 mm, respectively, with a 2-mm-wide null at center. The broad-beam and the narrow-beam lenses fragmented 44 ± 9% and 16 ± 4% (p = 0.007, N = 3) of a stone by weight, respectively, in the same duration at the same peak negative pressure. The method broadened the focus and improved the BWL rate of fragmentation of large stones.